New records for Brassicaceae for San Luis province (Argentina) (Semiárida, 2020)
In the present paper, 11 native and 5 introduced taxa belonging to Brassicaceae, and distributed among 7 genera are recorded for first time for San Luis province, Argentina, Common names, illustrations, habitat, distribution and herbarium specimens as a reference are provided tor each taxon. Also, a key to indentify species of the genus Lepidium are given.
Keywords: New records; Brassicaceae; San Luis; Argentine